Long-term incidence of colorectal cancer after bariatric surgery or usual care in the Swedish Obese Subjects study. - Magdalena Taube; Markku Peltonen; Kajsa Sjöholm; Richard Palmqvist; Johanna C Andersson-Assarsson; Peter Jacobson; Per-Arne Svensson; Lena M S Carlsson (PLoS ONE)
Bariatric surgery in patients with obesity is generally considered to reduce cancer risk in patients with obesity. However, for colorectal cancer some studies report an increased risk with bariatric surgery, whereas others report a decreased risk. These conflicting results demonstrate the need of more long-term studies analyzing the effect of bariatric surgery on colorectal cancer risk. Therefore, data from the Swedish Obese Subjects (SOS) study, ClinicalTrials.gov identifier: NCT01479452, was used to examine the impact of bariatric surgery on long-term incidence of colorectal cancer. The SOS study includes 2007 patients who underwent bariatric surgery and 2040 contemporaneously matched controls who received conventional obesity treatment. Patients in the surgery group underwent gastric bypass (n = 266), banding (n = 376) or vertical banded gastroplasty (n = 1365). Information on colorectal cancer events was obtained from the Swedish National Cancer Registry. Median follow-up was 22.2 years (inter-quartile range 18.3-25.2). During follow up there were 58 colorectal cancer events in the surgery group and 67 colorectal cancer events in the matched control group with a hazard ratio (HR) of 0.79 (95% CI:0.55-1.12; p = 0.183). After adjusting for age, body mass index, alcohol intake, smoking status, and diabetes, the adjusted HR was 0.89 (95% CI:0.62-1.29; p = 0.551). When analyzing rectal cancer events separately- 19 events in the surgery group and 31 events in the control group-a decreased risk of rectal cancer with surgery was observed (HR = 0.56; 95% CI:0.32-0.99; p = 0.045, adjusted HR = 0.61 (95% CI:0.34-1.10; p = 0.099), while the risk of colon cancer was unchanged. To conclude- in this long-term, prospective study, bariatric surgery was not associated with altered colorectal cancer risk.